Preoperative systemic inflammatory response index predicts long-term outcomes in type B aortic dissection after endovascular repair - Zhao, Yufei; Hong, Xiang; Xie, Xinsheng; Guo, Daqiao; Chen, Bin; Fu, Weiguo; Wang, Lixin (Frontiers in Immunology, 2022)
Objectives: Inﬂammation is a hallmark of the initial development and progression of aortic dissection. This study aimed to investigate the value of preoperative inﬂammatory biomarkers in predicting aorta-related adverse events (AAEs) after thoracic endovascular aortic repair (TEVAR) for type B aortic dissection. Methods: We included all patients who underwent TEVAR for type B aortic dissection between November 2016 and November 2020 in this single-centre, retrospective cohort study. Patients were divided into two groups: the AAEs group (n = 75) and the non-AAEs group (n = 126). Postoperative inﬂammatory biomarkers were recorded, including neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), platelet-to-lymphocyte ratio (PLR), systemic immune inflammation index (SII), and systemic inflammatory response index (SIRI). Patients were followed-up for the development of AAEs. Prediction accuracy of inflammatory biomarkers for AAEs were evaluated using the area under the receiver operating characteristic curves. Results: This study included 201 patients, of whom 80.0% were men, with a mean age of 59.1±12.5 years. A total of 75 patients developed AAEs after TEVAR. The AUCs of NLR, MLR, PLR, SII, and SIRI for AAEs were .746, .782, .534, .625 and .807, respectively. Age and SIRI were independent risk factors for the AAEs after TEVAR (HR 3.264, p < .001; HR 4.281, p < .001, respectively). Survival analysis revealed signiﬁcantly lower AAE-free status in patients with preoperative SIRI > = 4 (p < .001). Conclusion: Increased preoperative SIRI and age are independent risk factors for AAEs after TEVAR in type B aortic dissection.